Diamond dilemma : shaping Korea for the 21st century - Hussain, Tariq; Hussain, Tariq (Seoul, Korea : Seoul Selection, 2008)
Political planning |z Korea (South) 651 _0 |a Korea (South) |x Politics and government |y 2002- 651 _0 |a Korea (South) |x Economic policy |y 1988- 651 _0 |a Korea (South) |x Economic conditions |y 1988-
Includes index.
aHussain, Tariq. 245 10 $aDiamond dilemma $b: shaping Korea for the 21st century / $cTariq Hussain. 260 $aSeoul : $bSeoul Selection, $c2008. 300 $a262 p. 650 4 $aSituación económica. 650 4 $aHistoria 651 $aCorea (República)
General
Keywords: Political planning -- Korea (South); Korea (South) |x Politics and government |y 2002- -- Politics and government -- 2002-; Korea (South) -- Economic policy -- 1988-; Korea (South) -- Economic conditions -- 1988-